Bioactive Compounds via in vitro Culture Approach and Pharmacological Attributes of Genus Euphorbia: A Comprehensive Review - Noor Zaman; Sami Ullah; Wadood Shah; Muhammad Nauman Khan; Baber Ali; Amjad Ali; Fethi Ahmet Ozdemir; Gaweł Sołowski (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The family Euphorbiaceae comprises 2000 species and is listed as third among the largest flowering family. Euphorbia is used in traditional treatment for various diseases, including dengue fever, dysentery, diarrhea, and anemia. This review aimed to collect data from various published literature sources for quick and effective cultivation of Euphorbia species through tissue culture and documentation of potent secondary metabolites obtained from different cultures of Euphorbia and its manifold pharmacological activities from various parts extracts. The data for this review were systematically collected from different scientific databases, including Google Scholar, Science Direct, PubMed, and published literature. Different secondary metabolites have been reported from the in votro culture of Euphorbia containing anthocyanin, saponins, tannins, sterols, ﬂavonoids, glycosides, diterpenes, and sesquiterpene. The essential oils from extractions of the Euphorbia genus embraced about 80 active phytochemical constituents. The extracts and compounds exhibited different pharmacological activities, including hepato-protective, anti-fungal, anti-bacterial, and anti-cancer. Besides the pharmaceutical and importance of the genus Euphorbia, this report also described the methodologies of explant cultures, in-vitro production of biologically active compounds, and vital phytochemicals extraction from various parts of Euphorbia. Therefore, there is a need for in-vivo studies on Euphorbia to be further investigated to confirm the therapeutic effects for safe and effective medical use. The in-vitro cultivation techniques need further development, either in bioreactors or temporary immersions and shake flasks, to obtain vigorous sprouts of Euphorbia.